The Durability of Compliance Under External Accountability: The Case of the Police Data Initiative - Choi, Tae-Ung; Kim, Minjae (Organization Science, 2026)
External accountability initiatives, which combine public disclosure of internal information with enforcement, are widely regarded as useful instruments to effect organizational compliance with external demands. Yet, even though such compliance may be fruitful only if it persists, its durability has been assumed rather than directly tested. We report on such direct tests, using the Police Data Initiative (PDI). Launched across the United States in 2015 to “decrease inappropriate uses of force,” especially against Black citizens, the PDI mandated the release of traffic stop data and increased oversight of participating local police departments. A difference‐in‐differences analysis across 36 police departments shows that PDI adoption initially reduced stops, especially in neighborhoods with more Black residents. Over time, however, these treated departments reversed course and ultimately increased stops, particularly in said neighborhoods. This backsliding was more pronounced in departments with higher pre-PDI stop rates and larger racial disparities. Our findings show limited durability of compliance under external accountability and identify conditions under which external accountability reinforces entrenched patterns over time. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2024.18975 .